From the “scriitorii progresişti” to the boom: Romania and the globalization of Latin American literature in the socialist world (1964-1971) (Anclajes, 2023)
The Cold War motivated the international cultural field to replicate the geopolitical tensions and affinities that gripped the world. The positive side of this process contributed to the expansion of national literatures in environments where traditionally they had not found great resonance. However, the perverse effects were translated into various exclusions and dogmatic impositions that undermined the autonomy of writers. Latin American literature experienced, in this context, a process of globalization. The aim of this text is to testify to the complexities inherent to the reception of this literature in socialist Romania, for which a remarkable set of periodicals is analyzed, especially from 1964 to 1971. The translation, edition and physical reception of the Latin American authors themselves it was produced according to changing structural determinations, which show the evolution of the Romanian political-cultural field itself, but also thanks to individual gatekeepers who brought Latin American literature closer to the Romanian public.
Keywords: Eastern bloc; boom; Latin American literature; Romania; translation